Highly Oxygenated Labdane Diterpenoids from Stevia rebaudiana and Their Anti‐Atherosclerosis Activities. Issue 1 (21st December 2022) - Cheng, Bin; Fang, Fei; Zhou, Qin‐Tao; Li, Yan; Wu, Xue‐Wen; Zhao, Xue‐Rong; Bi, De‐Wen; Zhang, Xing‐Jie; Zhang, Rui‐Han; Ji, Xu; Li, Xiao‐Li; Cao, Guang; et al.
Abstract: Five unknown labdane diterpenoids Stevelins A–E (1–5 ), three known labdane diterpenoids (6–8 ) and three labdane norditerpenoids (9–11 ) were isolated from the Stevia rebaudiana . The structures were determined primarily via NMR spectroscopic data and HR‐ESI‐MS experiments. X‐ray crystallography using Cu K α radiation was used to determine the absolute configurations of 1, and the absolute configurations of 2–5 were deduced by electronic circular dichroism (ECD) calculations. The potential anti‐atherosclerosis activities of all compounds were evaluated by measuring their inhibitory effects on the macrophage foam cell formation. As a result, most isolated compounds could significantly inhibit oxidized low‐density lipoprotein (ox‐LDL)‐induced macrophage foam cell formation, which suggests that these compounds may be promising candidates in the treatment for atherosclerosis. Abstract :